Heat Stress: Effects on Rumen Microbes and Host Physiology, and Strategies to Alleviate the Negative Impacts on Lactating Dairy Cows - Kim, Seon Ho; Ramos, Sonny C.; Valencia, Raniel A.; Cho, Yong Il; Lee, Sang Suk (Frontiers in Microbiology, 2022)
Heat stress (HS) in dairy cows causes considerable losses in the dairy industry worldwide due to reduced animal performance, increased frequencies of metabolic disorders, altered rumen microbiome and other health problems. It decreases ruminal pH and acetate concentration, while increases ruminal lactate concentration. Heat-stressed cows have an increased abundance of lactate-producing bacteria like Streptococcus and unclassified Enterobacteriacea, and soluble carbohydrate utilizers like Ruminobacter, Treponema, and unclassified Bacteroidaceae. Cellulolytic bacteria, especially Fibrobacteres, increases during HS due to higher heat resistance than others. Actinobacteria and Acetobacter, both acetate-producing bacteria, decreases during HS condition. Rumen fermentation functions, blood parameters, and metabolites are also affected by physiological responses of the animal to HS. Isoleucine, methionine, myo-inositol, lactate, tryptophan, tyrosine, 1,5-anhydro-D-sorbitol, 3-phenylpropionic acid, urea, and valine decreases during this condition. These responses affect feed consumption and production efficiency in milk yield, growth rate, and reproduction. In cellular level, activation of heat shock transcription factor (HSF) and increased expression of heat shock proteins (HSPs) are the usual response to cope homeostasis. HSP70 is the most abundant HSP family responsible for environmental stress response, while HSF1 has an essential function of increasing cell temperature. The expression of bovine lymphocyte antigen and histocompatibility complex, class II, DRB3 downregulates during HS while HSP90 beta I and HSP70 1A upregulates. HS increases the expression of cytosolic arginine sensor for mTORC1 subunits 1 and 2, and phosphorylation of mammalian target of rapamycin, and decreases the phosphorylation of Janus kinase-2, a signal transducer and activator of transcription factor-5. These changes in physiology, metabolism, and microbiomes in heat-stressed dairy cows requires urgent alleviation strategies. Establishing control measures to combat HS can be facilitated by elucidating mechanisms, such as proper HS assessment; access to cooling facilities; special feeding and care; efficient water systems; and supplementation with vitamins, minerals, plant extracts, and probiotics. Understanding the relationship between HS and rumen microbiome could contribute to developing manipulation strategies to alleviate the influence of HS. This review comprehensively elaborates the impact of HS in dairy cows and introduces different alleviation strategies to minimize HS, thus restoring the rumen microbiome disrupted by this condition.